NAFKAH PERSPEKTIF FIQIH DAN UNDANG-UNDANG ; - Sokhi Huda; Ahmad Halimi Masruri (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2022)
This article is the result of a qualitative field research. This research is a legal sociology research. This article discusses the neglect of livelihoods that occurred in Gedang Hamlet, Tambakrejo Village. Researcher analyzes the research data with fiqh theory and the Undang-undang Perkawinan No.1 1974. The findings of this study are that the neglect of livelihood that occurs in Gedang Hamlet, Tambakrejo Village is included in the category of violation of the income obligation, it can even be included as domestic violence. There are two things to be argued. Ms. LM's husband has not given her a living for 6 months, the second is that Mrs. LM's husband often comes home at night, sometimes even for several days he does not come home. fiqh clearly mentions the categories of earning a living, although with many variations. All fiqh differences of opinion about the limits of living were violated by LM's mother's husband. Law No. 23 of 2004 was also violated in terms of fulfilling the husband's support for his wife. Keyword: living limits, fiqh, the rule of law Daftar Pustaka ------------- Al qur’an karim. Departemen Agama, tahun 2015. Al Amin, Habibi. "Guardians Concept in Qur'an Perspective." Shakhsiyah Burhaniyah: Jurnal Penelitian Hukum Islam 6.1 (2021): 95-114. Al Amin, Habibi. "Penciptaan Adam; Mendialogkan TafsiR Marah Labid dengan Teori Keadilan Gender." An-Nuha: Jurnal Kajian Islam, Pendidikan, Budaya Dan Sosial 1.1 (2014): 17-44. Al Amin, Habibi. "Tafsir Sufi Lataâ€™ if al-Isyarat." SUHUF 9.1 (2016): 59-77. Al Anshary, Zakariyya. Fath al Wahhab, Jilid II (Beirut: Dar Al Kutub Al-lmiyyah, 1418) Asqalani, Ibnu hajar. Al- Bulughul Maram, Beirut: Maktabah At-Tijarah Al-Kubra, t,t, Ghozali, Abdul Rahman. Fiqih Munakahat. Jakarta : Kencana. 2003. Hanbal, Ahmad Bin Muhammad Bin. Musnad Ah}mad (Beirut: Muassasah al Risa>lah, 2001) Hasfakiy, al-Durr al-Mukhtar, (Beirut: Da>r al-Fikri, 1386 H) Husaini,Abu bakar Taqiyuddin bin Muhammad al-. Kifayat al-Akhyar (Kelengkapan orang Shaleh), (Surabaya; Bina Ilmu, t.t.) Imron, Abu Amar. Fathul Qarib, Menara Qudus, t.t Jaziri, Abdurrahman al-,. kitab al-Fiqh ‘ala Madzhabi al-Arba’ah, (Beirut: Dar al-Kutub al-‘Ilmiyah, 1969) Ma’ruf ,Amin, dkk,. Himpunan Fatwa Majelis Ulama Indoneisa sejak 1975, tt, Erlangga, Jakarta. Matodang, Fatma Novida. Konsep Nusyuz Suami dalam Perspektif Hukum Perkawinan Islam, Tesis (Medan: Universitas Sumatera Utara: 2009) Qozainiy ,Abu Abdillah Muhammad bin Yazid al-,. Sunan Ibnu Majah Juz II (tt, Dar Ihya al kutub al-arabiyah, tth), Shabuni, Muhammad Ali, Rawa’i al-Bayan fi Tafsir Ayat al-Ahkam, Cet ke-3, (Kairo: Darul Kutub al-Arabiyah, 1992) Shan’ani, Muhammad bin Ismail al-Kahlani Subul al-Salam, Juz III, (Kairo: Dar al-Fikr, tt) Syatha, Abu Bakar bin Sayyid Muhammad. I’anah at}-T{a>libin, (Beirut: Dar al Fikr, tt.) Taufiqurrahman, Zaky Fajar, and Habibi Al Amin. "Desain Pembelajaran Literasi Kitab Kuning Melalui Metode Sorogan dalam Meningkatkan Pemahaman Agama Islam." Syntax Literate; Jurnal Ilmiah Indonesia 6.2 (2021): 1467-1474. Zuhayliy, Wahbah al-Tas>r al-Muni>r Fi> al-‘Aqi>dah Wa al-Shari>’ah Wa al-manhaj Vol XIV (Damaskus : Da>r al-Fikr)